661. Surveillance of Rabies Prophylactic Treatments After Exposure to Animals: 5 Years Experience. (26th November 2018) - Dougas, Georgios; Konte, Vasileia; Mitrou, Konstantinos; Christodoulou, Emmanuel; Stavrakakis, Michail; Baka, Agoritsa; Georgakopoulou, Theano; Metallidis, Symeon; Istikoglou, Ioannis; Pargiana, Chrysa; Liona, Aikaterini; Tsalikoglou, Foteini; et al.
Abstract: Background: Rabies re-emerged in Greek fauna in October 2012, 25 years after the last report in animals. Hellenic Center for Disease Control & Prevention developed a semi-active surveillance system to monitor the medical management of potentially exposed persons to rabies. This study aims to providing insight on the biologicals administered and the epidemiological characteristics of the cases where post-exposure prophylaxis was initiated after contact with animals. Methods: Data received from November 2012 to December 2017 on demographics, exposure event, animal species involved, category of exposure (COE) according to WHO, vaccination history, the veterinary evaluation of the animal and the type of treatment administered, were analyzed with Epidata Analysis V.2.2.2.180. Results: A total of 1, 616 cases (63.2% males) received rabies post-exposure prophylaxis. In 94.7% of cases cleansing of the wound before visiting a medical practitioner took place during the first 3 hours after the exposure whereas 75.1% of victims presented at a healthcare setting during the first 24 hours; COE III cases had shorter time interval ( P < 0.01), before arrival at a hospital (mdn = 1.3 hours) compared with COE II (mdn = 3.6 hours) or COE I (mdn = 88.2 hours) (Figure 1); 55.1% were initiated on a vaccine series, 43.1% received both vaccine and immunoglobulin and 1.7% immunoglobulin alone. Exposure to stray dogs represented 67.3% of all incidents (Table 1). No human case was recorded. Conclusion: The vast majority of the reported treatments involved stray dogs as Greek legislation permits free roaming of ownerless companion animals in urban settings. Bat was the fourth most frequently reported species in our treatment series. Surveillance of post-exposure prophylaxis represents a valuable tool for outlining the epidemiological profile of treated cases and for planning of effective policies for the management of rabies. Disclosures: All authors: No reported disclosures.